Detection of Hemoglobinopathies in Cuban Pregnant Women from the Program: Sickle Cell Anemias in Cuba - Yadira Valdés Fraser; Tatiana Acosta Sánchez; Jacqueline Pérez Rodríguez; Beatriz Suárez Besil; Sandra Bárbara Correa Jiménez (Universidad de las Ciencias Médicas de Cienfuegos, 2024)
Foundation: prenatal detection of hemoglobinopathies in Cuba is performed on all pregnant women in Pri-mary Health Care, through hemoglobin electrophoresis to identify high-risk couples. The program provides genetic counseling, molecular prenatal diagnosis and selective interruptions of affected fetuses, at the re-quest of couples. Objective: determine the type and frequency of hemoglobinopathies in Cuban pregnant women. Method: a descriptive, retrospective and cross-sectional study was carried out to determine the type of hemoglobinopathies in 1,342,917 pregnant women recruited over a period of ten years. The research meth-od was hemoglobin electrophoresis in agarose gels at alkaline pH. Confirmation by electrophoresis of hemo-globin in agarose gel at acidic pH, both methods using the Hydrasys 2 equipment. Results: the overall frequency of pregnant women with hemoglobinopathies was 3.5 %. Hemoglobinopa-thies were detected in 47,465 women; 38,698 with heterozygous S variant, 8,706 hemoglobin C variants and 158 other variants. 44,283 husbands with hemoglobinopathies were detected, 3,099 high-risk couples were detected, and 2,689 molecular prenatal diagnoses were performed. 522 affected fetuses were confirmed and 382 couples requested termination of pregnancy. The program reached 99.24 % coverage in the country. Conclusions: the detection of hemoglobinopathies in pregnant women residing in Cuba allowed us to know the type of hemoglobinopathy and the frequency of abnormal hemoglobins and new variants, hence the in-terest in continuing the research program to prevent the appearance of severe forms of the disease.